Use of Perforator Propeller Flaps for Coverage of Soft issue Defects Around The Distal Leg and Ankle (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Introduction: Perforator propeller flap is a suitable option to cover soft tissue defects in the distal leg and ankle which preserves the main vascular arteries of the lower extremity and muscle function. The aim of this study is to evaluate the use of perforator propeller flaps for coverage of soft tissue defects around the distal leg and ankle.Methods: This prospective study was donebetween December 2018 to November 2019in the Department of Burn & Plastic Surgery of National Institute of Traumatology and Orthopedic Rehabilitation ( NITOR), Dhaka. Total 32 patients with small to medium sized soft tissue defect over distal leg and ankle underwent reconstruction with perforator propeller flaps. Sixteen patients had defect over tendo achilles area, 6 had defect over lateral malleolus,7 over medial malleolus and medial aspect of distal third leg and only 3 had defect in front of ankle. Average Flap length and width were 12.72 (+4.19) & 5.63 (+1.78) cm respectively. Flap rotation was measured 180 degrees in 84.37% of the cases. The propeller flaps were based on a single perforator and it was observed from the posterior tibial artery in 62.5% and peroneal artery in 37.5% of the cases.Results: 81.25% of the flaps completely survived. Total flap loss was observed in one case (3%) while partial flap loss occurred in 6.2% cases. Marginal flap necrosis and epidermolysis were observed in 6.2% and 3% cases respectively.Conclusions: Propeller flapshavereliable vascular pedicle as well as greater freedom in design and arc of rotation that extend the possibility ofreconstructing difficult wounds with local tissues and minimal donor-site morbidity.J Bangladesh Coll Phys Surg 2021; 39(2): 87-93